2012
DOI: 10.1038/ki.2011.305
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin triggers inflammation and increased peritoneal permeability leading to peritoneal fibrosis

Abstract: Long-term peritoneal dialysis induces peritoneal fibrosis with submesothelial fibrotic tissue. Although angiogenesis and inflammatory mediators are involved in peritoneal fibrosis, precise molecular mechanisms are undefined. To study this, we used microarray analysis and compared gene expression profiles of the peritoneum in control and chlorhexidine gluconate (CG)-induced peritoneal fibrosis mice. One of the 43 highly upregulated genes was pleiotrophin, a midkine family member, the expression of which was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 40 publications
3
51
0
1
Order By: Relevance
“…PTN is also involved in inflammatory pathologies (Pantazaka and Papadimitriou, 2012;Papadimitriou et al, 2009;Silver et al, 2012;Yokoi et al, 2012;Zhang et al, 2013) and activation of XO might be one of the mechanisms of its pro-inflammatory effects. In favor of this notion are data showing that interferon gamma (IFNγ), which is a known inducer of XO (Dupont et al, 1992), up-regulates PTN expression in capillaries of human atherosclerotic plaques through JAKs/STATs downstream effectors (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTN is also involved in inflammatory pathologies (Pantazaka and Papadimitriou, 2012;Papadimitriou et al, 2009;Silver et al, 2012;Yokoi et al, 2012;Zhang et al, 2013) and activation of XO might be one of the mechanisms of its pro-inflammatory effects. In favor of this notion are data showing that interferon gamma (IFNγ), which is a known inducer of XO (Dupont et al, 1992), up-regulates PTN expression in capillaries of human atherosclerotic plaques through JAKs/STATs downstream effectors (Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotrophin (PTN) is a heparin binding growth factor with a significant regulatory role on inflammation, angiogenesis and cancer (Pantazaka and Papadimitriou, 2012;Papadimitriou et al, 2009;Silver et al, 2012;Yokoi et al, 2012;Zhang et al, 2013). In all cases, the best characterized PTN function is its effect on cell migration through its receptor protein tyrosine phosphatase beta/zeta (RPTPβ/ζ) (Lu et al, 2005;Polykratis et al, 2005) and integrin alpha v beta 3 (α ν β 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…22,29 Immunohistochemistry found that GFP þ MCs begin to express ACTA2 1 day after a single CG injection ( Figure 2C). After three CG injections, GFP þ cells were observed in the connective tissue, and the cells showed fibroblastic structure and expressed ACTA2 ( Figure 2C).…”
Section: Differentiation Of Mcs Into Myofibroblasts In Peritoneal Fibmentioning
confidence: 99%
“…22,29 We examined whether 10 CG injections into the peritoneal cavity also causes injury to MCs in the liver as a visceral organ. With the use of the same Wt1…”
Section: Cg Causes Liver Injurymentioning
confidence: 99%
“…Lower doses of CG or shorter time courses produced milder and more infrequent development of peritoneal fibrosis [99,100]. Recent studies showed that a standard peritoneal fibrosis model could be produced in mice following treatment with 0.1% CG every other day or three times a week for 1-3 weeks [101][102][103][104][105][106][107][108].…”
Section: Zymosan-induced Fungal Peritonitis Modelmentioning
confidence: 99%